Cognitive-learning styles conceptual framework in vocational education - Mohamad, Mimi Mohaffyza; Yee, Mei Heong; Tee, Tze Kiong (Medwell Journals, 2017)
This study was conducted to analyze how learning styles influence the students’ academic achievement based on cognitive mastery and vocational elements. Descriptive case study was applied with quantitative and semi-structured interview as supporting components in this study. The quantitative data were gathered based on Felder and Silverman Learning Styles Model (FSLSM), Felder-Soloman Index of Learning Styles (ILS) and vocational cognitive elements which consist of the aspects of knowledge, skills and problem solving were taken into account in constructing the question items. Respondents from Vocational Colleges were involved in this study. Purposive sampling was used to select the schools and stratified sampling procedure was applied in the selection of 128 students as research respondents. Purposive sampling was also chosen to select teachers as respondents for interview. The study discovered that students tend to be visual learners. Visual learners represent the input dimension of FSLSM and the result showed there are significant differences between input dimension with skills and problem solving but not with knowledge. The discussions with teachers revealed that most teachers accommodate students learning styles with cognitive mastery by using visual approach to increase students’ academic achievement.